Recognizing of the language situation of a bilingual and multilingual child using the speech therapy questionnaire for recognizing a child’s language situation in the perspective of multilingualism and multiculturalism - Zawadka, Joanna; Kurowska, Marlena; Sadowska, Elżbieta (Interdyscyplinarne aspekty diagnozy i terapii logopedycznej, 2020)
In the article, we present the assumptions of the Logopedyczny kwestionariusz rozpoznania sytuacji językowej dziecka w perspektywie wielojęzyczności i wielokulturowości (Zawadka, Kurowska, Sadowska, in print), which is a tool supporting an in-depth parent interview for initial speech and language evaluation in the event of suspected difficulties in developing speech and language in children growing up in a multilingual and multicultural environment.